2020
DOI: 10.1177/2374373520926098
|View full text |Cite
|
Sign up to set email alerts
|

What Male Caregivers of Women With Breast Cancer Want in an Online Intervention: A Qualitative Study

Abstract: The diversity in cancer caregiver responsibilities often leaves caregivers feeling ill-prepared for their role. To inform the development of an online caregiver training intervention, we examined the views of men caring for a woman with breast cancer on intervention mode, timing, and content preferences. Thirteen men participated in a qualitative interview. The findings reveal that an online intervention should include educational content and psychological support, be interactive and personalized, and be avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Experts also suggested adding information related to hereditary/genetic information and lymphoedema screening which were not suggested by male caregivers in our formative study 10 . Inclusion of hereditary information is supported by a qualitative study of 50 informal caregivers of women with BC (74% were male), which found genetic risk to be a higher priority than self‐care, psychosexual concerns and caring responsibilities 28 .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Experts also suggested adding information related to hereditary/genetic information and lymphoedema screening which were not suggested by male caregivers in our formative study 10 . Inclusion of hereditary information is supported by a qualitative study of 50 informal caregivers of women with BC (74% were male), which found genetic risk to be a higher priority than self‐care, psychosexual concerns and caring responsibilities 28 .…”
Section: Discussionmentioning
confidence: 97%
“…29 Experts also suggested adding information related to hereditary/ genetic information and lymphoedema screening which were not suggested by male caregivers in our formative study. 10 � Defining the nature of the relationship between the male caregiver and care-recipient (e.g., partner, son, etc.) so information is better tailored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations